MADRASAH DINIYAH TAKMILIYAH DALAM PERSPEKTIF STANDAR PELAYANAN MINIMAL DI KABUPATEN CIREBON: MADRASAH DINIYAH TAKMILIYAH IN MINIMUM SERVICE STANDARDS PERSPECTIVE IN CIREBON - Abdul Basid (Penamas, 2015)
This paper presents the results of research on Minimum Service Standards in the implementation of Islamic non-formal education, Madrasah Diniyah Takmiliyah Awaliyah (MDTA). In an attempt to see the indication of services standards, this study uses a comparative research for eight Madrasahs Diniyah Takmiliyah, namely; MDTA Daar al Tawhid, Kampung Damai, Sebelas Bintang, Darul Ikram, Nasyrul Ulum, al-Faqih, an-Nidhamiyah, and Darussalam. This study employed a qualitative and quantitative approach. The results shows that management of MDTA has not fully met Minimum Service Standards, which has been determined by the letter of decree of Director General of Islamic Education number 3201. Although, it has not fully reached the standard, there are efforts from the madrasah and the region to improve diniyah education services for community. Local Government demonstrates support and spirit to Madrasah Diniyah Takmiliyah in order to be exist despite their limitations. Keywords: Madrasah Diniyah, religious education, Minimum Service Standards, Cirebon. Tulisan ini menyajikan hasil penelitian mengenai Standar Pelayanan Minimal (SPM) dalam Penyelenggaraan Madrasah Diniyah Takmiliyah (Awaliyah). Untuk mengetahui indikasi tersebut, dilakukan riset komparatif pada delapan Madrasah Diniyah Takmiliyah, yaitu; MDTA Daar al-Tauhid, Kampung Damai, Sebelas Bintang, Darul Ikram, Nasyrul Ulum, al-Faqih, an-Nidhamiyah, dan Darussalam. Penelitian ini menggunakan pendekatan kualitatif dengan didukung data kuantitatif. Hasil penelitian menunjukkan, penyelenggaraan MDTA belum sepenuhnya memenuhi SPM yang telah ditentukan oleh SK Dirjen Pendis Nomor 3201. Meskipun belum sepenuhnya mencapai SPM, namun ada upaya madrasah dan daerah untuk meningkatkan layanan pendidikan diniyah untuk masyarakat. Hal itu ditunjukkan dukungan Pemerintah Daerah dan semangat untuk tetap eksis dalam segala keterbatasan yang dimiliki oleh Madrasah Diniyah Takmiliyah.Kata Kunci: Madrasah diniyah, pendidikan keagamaan, Standar Pelayanan Minimal (SPM), Cirebon.